2014
DOI: 10.1089/tmj.2013.0219
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education Self-Management During Surgical Recovery: Combining Mobile (iPad) and a Content Management System

Abstract: Objective: The objective of this investigation was to assess whether a new electronic health (e-health) platform, combining mobile computing and a content management system, could effectively deliver modular and ''just-in-time'' education to older patients following cardiac surgery. Subjects and Methods: Patients were provided with iPad Ò (Apple Ò , Cupertino, CA) tablets that delivered educational modules as part of a daily ''to do'' list in a plan of care. The tablet communicated wirelessly to a dashboard wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 20 publications
5
57
0
6
Order By: Relevance
“…A recent qualitative study suggested stroke survivors found such interventions helpful and acceptable [18]. While mobile devices have been introduced in the acute care setting to promote patient education and engagement [19, 20], there have been no studies using mobile platform technologies for communication therapy, specifically within the first 14 days following stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative study suggested stroke survivors found such interventions helpful and acceptable [18]. While mobile devices have been introduced in the acute care setting to promote patient education and engagement [19, 20], there have been no studies using mobile platform technologies for communication therapy, specifically within the first 14 days following stroke.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Learners and faculty alike use mobile technology in patient care, 3,4 and uses include reviewing patient data on rounds, entering orders, and reviewing records. 5,6 In addition to enhancing patient care, mobile technology has been used to facilitate education.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies are showing that tablet computers can improve physicians practice as well as patient engagement. [5][6][7][8][9] While Apple iPad had an early dominance among the tablet market, Android tablets started to catch up in market share and expected to have around 60% of the tablet computer market compared to iPad at about 33% and Windows at 5% [10]. Google Android, Apple iOS and Microsoft Windows now represent the three major operating system platform for tablet computers.…”
Section: Introductionmentioning
confidence: 99%